DEVELOPMENT OF A MULTISENSORY LEARNING MEDIA BASED ON LIFT THE FLAP AUDIO BOOK TO ENHANCE BASIC ARABIC LANGUAGE SKILLS OF 7TH GRADE STUDENTS AT SMP PAHLAWAN NASIONAL MEDAN - Annisa Annisa; Fahrurrozi S (Ihya al-Arabiyah: Jurnal Pendidikan Bahasa dan Sastra Arab, 2025)
Basic Arabic language learning at SMP Pahlawan Nasional Medan is still limited because it is not included in the formal curriculum, although students' interest is quite high. This condition creates a gap between students' learning motivation and the availability of engaging learning media suitable for the characteristics of middle school students. This study aims to develop and examine the effectiveness of a multisensory learning media based on the Lift the Flap Audio Book to improve basic Arabic language skills for seventh-grade students. This research employed a Research and Development (R&D) method using the ADDIE model, which includes the stages of Analyze, Design, Develop, Implement, and Evaluate. Data were collected through observations, interviews, expert validation questionnaires (both content and media experts), as well as pre-tests and post-tests of students, and analyzed quantitatively and qualitatively. The results show that the developed media is feasible and effective. Content expert validation scored 75% (quite feasible), and media expert validation scored 95.45% (very feasible). The small group trial obtained a student response of 84.5% (very good), while the large group trial showed an increase in average scores from 55.8 to 82.4 with an N-Gain of 0.64 (medium-high category). In conclusion, the Lift the Flap Audio Book effectively improves students' listening, reading, and pronunciation of basic Arabic vocabulary, while providing an interactive, enjoyable, and student-centered learning experience.